Rhythm control agents and adverse events in patients with atrial fibrillation. - Taylor, C; Hodgkinson, J; Hobbs, F (2010)
BACKGROUND: Atrial fibrillation (AF) is the commonest rhythm disorder and has major impact on patients. Controversy remains about the best treatment strategy between rate and rhythm control (in addition to adequate thromboprophylaxis). Rhythm control agents are associated with clinically important adverse events. AIM: The aim of this study was to assess the risk of adverse events in patients with AF receiving rhythm control agents. DESIGN OF STUDY: This is a retrospective case control note review and outcome linkage analysis. SETTING: Setting of this study included patients with a diagnosis of AF receiving amiodarone, flecainide or sotalol in practices registered with the General Practice Research Database (GPRD) in the UK. METHOD: This is a retrospective case control note review and outcome linkage analysis on the GPRD routine clinical dataset to evaluate the adverse events and predictors of treatment discontinuation in patients using licenced rhythm modifying medication. RESULTS: Adverse events are more common in patients currently or previously taking amiodarone, flecainide or sotalol than age- and gender-matched controls. All three antiarrhythmics were associated with increased all-cause mortality. Congestive heart failure was more common in all amiodarone and sotalol users as well as past users of flecainide. Thyroid disease was more common in patients treated with amiodarone and sotalol but only amiodarone had an increased risk of pulmonary toxicity. The number of patients with liver failure was too small in all cases for statistical analysis. CONCLUSION: The rhythm control agents amiodarone, flecainide and sotalol have significant adverse effects which can lead to discontinuation of their use. This should be considered when deciding the most appropriate treatment option for patients with AF.